2015
DOI: 10.1371/journal.pone.0121835
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine Destabilizes Oral Multi-Species Biofilm Communities Developed in Human Saliva

Abstract: The amino acid L-arginine inhibits bacterial coaggregation, is involved in cell-cell signaling, and alters bacterial metabolism in a broad range of species present in the human oral cavity. Given the range of effects of L-arginine on bacteria, we hypothesized that L-arginine might alter multi-species oral biofilm development and cause developed multi-species biofilms to disassemble. Because of these potential biofilm-destabilizing effects, we also hypothesized that L-arginine might enhance the efficacy of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 62 publications
9
80
0
Order By: Relevance
“…In addition to providing bulk and mechanical stability, the EPS matrix also forms a diffusion-limiting milieu that embeds cariogenic bacteria, forming protective niches against antimicrobials (1,6,55). Recently, it was shown that the antimicrobial efficacy of cetylpyridinium chloride (CPC) against oral biofilms was enhanced when used in combination with arginine in vitro (27). The authors suggested potential alterations in the EPS matrix, which could facilitate CPC penetration (27); our data certainly support this clinically relevant observation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to providing bulk and mechanical stability, the EPS matrix also forms a diffusion-limiting milieu that embeds cariogenic bacteria, forming protective niches against antimicrobials (1,6,55). Recently, it was shown that the antimicrobial efficacy of cetylpyridinium chloride (CPC) against oral biofilms was enhanced when used in combination with arginine in vitro (27). The authors suggested potential alterations in the EPS matrix, which could facilitate CPC penetration (27); our data certainly support this clinically relevant observation.…”
Section: Discussionsupporting
confidence: 64%
“…These findings suggest the possibility of arginine supplementation as a strategy to disrupt pathogenic biofilms. In vitro studies show that exogenous L-arginine can inhibit the adhesion of S. mutans to saliva-coated surfaces (25), influence single-species S. gordonii biofilm formation (26), and destabilize a saliva-derived biofilm community (27). Arginine treatments also increased arcA gene (involved in arginine metabolism) abundance compared to that in untreated biofilms, indicating a potential role for the enrichment of alkali-producing microflora (28).…”
mentioning
confidence: 99%
“…Real-time PCR showed significant reductions in spaP expression (ϳ1.5-fold), while quantitative real-time PCR (qRT-PCR) and RNA-seq confirmed a significant decline in gtfB mRNA (Ͼ2-fold). The results from studies using mixed-species biofilm models of dental plaque containing S. mutans established that treatment with arginine alters the architecture of the biofilms by interfering with the proper production of EPS (mostly glucans and fructans) (27,30,41). Glucans are the key matrix components enabling S. mutans organisms to adhere to each other and to the tooth surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Many models have been developed in an attempt to simulate the oral cavity [55,[60][61][62]. Innovative strategies have been incorporated, such as using a salivary medium and/or teeth as the substratum, to more closely simulate the in vivo environment.…”
Section: Oral Microcosmmentioning
confidence: 99%